THE EFFECTIVENESS OF BACK MASSAGE AND ULTRASOUND THERAPY COMBINED WITH HOME-BASED EXERCISE IN REDUCING DISABILITY IN MECHANICAL LOW BACK PAIN - Saraswati, Putu Ayu SIta; Thanaya, Sayu Aryantari Putri; Nugraha, Made Hendra Satria (Sport and Fitness Journal, 2022)
Low back pain (LBP ) is a common problem and a leading  cause  of  disability  worldwide. Mechanical LBP is a cumulative process caused by physical workloads, errors when lifting, and poor posture while working, which causes the lower back to experience heavy mechanical stress. This can result in pain and limitation of motion in the lumbar spine, thereby increasing the level of disability. The combination of ultrasound therapy with back massage is often used in general to treat mechanical LBP. The addition of home-based exercise to this combination is expected to accelerate tissue repair, reduce pain, and increase the range of joint motion, and it is expected that disability will decrease. This study aimed to compare the combination of back massage and ultrasound therapy with or without home based exercise in reducing disability due to mechanical LBP. This single blinded randomized controlled trial was conducted for 4 weeks involving 24 subjects with mechanical LBP, who were randomly assigned to a treatment group or control group. Disability due to mechanical LBP was measured using the Modified Oswestry Disability Index (MODI), which was assessed at baseline and after the last treatment was given. After treatment, between-group analysis using the independent t-test found the mean reduction of MODI score significantly different between the intervention and control group after receiving the intervention. Therefore, it can be concluded that the addition of home-based exercise to back massage and ultrasound therapy can significantly reduce disability due to mechanical LBP.